2018
DOI: 10.1155/2018/3201940
|View full text |Cite
|
Sign up to set email alerts
|

The Progress of T Cell Immunity Related to Prognosis in Gastric Cancer

Abstract: Gastric cancer is the fifth most common malignancy all over the world, and the factors that can affect progress and prognosis of the gastric cancer patients are various, such as TNM stages, invasive depth, and lymph node metastasis ratio. T cell immunity is important component of human immunity system and immunity responding to tumor and dysfunction or imbalance of T cell immunity will lead to serious outcomes for body. T cell immunity includes many different types of cells, CD4+ T cell, CD8+ T cell, memory ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…The T cells CD4+ and CD8+ are important components of the acquired immune system. CD4+ cells, also known as helper T cells, influence the secretion of antibodies by B cells and regulate immune responses of other T cells, whereas CD8+ cells are major cytotoxic effector cells [28, 29]. Changes in the abundances or ratio of CD4+ to CD8+ T cells are reflective of the condition of the immune system whereby a high CD4+/CD8+ ratio indicates hyperactive cellular immune system and the inverse is related to immunosuppression [30].…”
Section: Discussionmentioning
confidence: 99%
“…The T cells CD4+ and CD8+ are important components of the acquired immune system. CD4+ cells, also known as helper T cells, influence the secretion of antibodies by B cells and regulate immune responses of other T cells, whereas CD8+ cells are major cytotoxic effector cells [28, 29]. Changes in the abundances or ratio of CD4+ to CD8+ T cells are reflective of the condition of the immune system whereby a high CD4+/CD8+ ratio indicates hyperactive cellular immune system and the inverse is related to immunosuppression [30].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the fourth most commonly diagnosed malignant tumor worldwide and considered as the third leading cause of cancer-related death, following lung and liver cancer ( 1 ). Despite a drop in the mortality rate due to the advancements of pathological diagnostic programs and therapeutic approaches, gastric cancer remains a prevalent disease with poor prognosis ( 2 , 3 ). Therefore, continuous attempts are urgently needed to discover new and effective targets for the clinical therapy of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The immune and hypoxia microenvironment plays a critical role in the tumorigenesis and progression of gastric cancer [10,11,[13][14][15]25]. On one hand, the immune incapability in the tumor microenvironment has been reported as an essential mechanism for solid cancers to evade from host immunity [13,15,[25][26][27]. It was found that higher expression of immune-related gene predicts better prognosis in both EBV-positive and EBV-negative gastric cancer patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been reported as one of characteristic hallmarks of solid tumors that directly contribute to the malignant properties of cancers, including tumor progression, invasion and metastasis [9][10][11][12]. Meanwhile, immune cell is also a potentially powerful force that can prevent or slow tumor growth, which is associated with tumor invasion and metastasis [13][14][15]. Interestingly, increasing evidences have found that the direct or indirect interaction between hypoxia and immune status in gastric cancer microenvironment [16,17], although their underlying mechanisms remains unclear.…”
mentioning
confidence: 99%